Proximal tibial osteotomy for the repair of cranial cruciate-deficient stifle joints in dogs - Damur, D. M.; Tepic, S.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A proximal tibial osteotomy technique for the repair of complete or partial rupture of the cranial cruciate ligament in dogs is described and the results of a series of 100 consecutively operated stifle joints are presented. Although the majority of dogs regained full function of the operated limb within four months of surgery, the overall complication rate was high.
Keywords: Osteotomy; cranial cruciate ligament rupture; stifle joint; dog